Computational Investigation of α-Glucosidase Inhibition by Phytochemical Compounds from Muntingia calabura L. Leaves: Insights into Potential Antidiabetic Agents - Syaiful Prayogi; Aulia Rahman; Tsaiatul Mahbubah; Nabilla Defira Putri Maisaan (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Diabetes Mellitus (DM) is a degenerative disease that poses a major global health problem. It is characterized by increased blood glucose levels (hyperglycemia). Common therapeutic agents for DM include sulfonylureas, biguanides, and α-glucosidase inhibitors. However, the use of α-glucosidase inhibitors is often associated with several issues such as the presence of non-intestinal α-glucosidase in various body cells, gastrointestinal side effects (diarrhea, bloating, abdominal discomfort), and high IC₅₀ values indicating low potency and efficacy against the α-glucosidase enzyme. This study aims to explore the potential of flavonoid compounds from Muntingia calabura L. (kersen) leaves as α-glucosidase inhibitors through in silico analysis. The study was conducted using molecular docking to evaluate the binding affinity and interaction of flavonoid compounds with the α-glucosidase enzyme. The docking results showed that 8 ligands test exhibited strong binding affinities, inhibitors constants, and stable interactions with the active site of α-glucosidase, comparable to standard inhibitors (acarbose). The two most promising ligands as α-glucosidase inhibitors were identified as 20,40-Dihydroxy-30-methoxydihydrochalcone (50) and (-)-30-Methoxy-20,40,β-trihydroxydihydrochalcone (51), exhibiting binding affinities and inhibition constants of –7.33 kcal/mol; 4.27 μM and –7.30 kcal/mol; 4.45 μM, respectively, have promising potential as natural α-glucosidase inhibitors and may serve as lead compounds for the development of new antidiabetic agents. Their inhibitory potential was further supported by favorable ADMET parameters and compliance with Lipinski’s rule of five. Further in vitro and in vivo studies are needed to confirm these findings.